Bashir Ahmad Khilji. Sixty Years of Human Resource Development in Pakistan. Government of Pakistan, Higher Education Commission, Pakistan. Islamabad: HEC Printing Press. 2011. 283 pages. Price not given. (The Pakistan Development Review, 2011)
Human resource development (HRD) occupies a central position in the advancement of a society. It is obvious from the historical experience of industrialised countries that developing human capacity is essential for a self-reliant and self-sustaining pattern of growth. Almost all Asian countries, including Pakistan, continue to search for additional appropriate strategies to respond to the rapid changes in the global economy. Unfortunately, despite registering a satisfactory rate of economic growth, Pakistan’s progress on the human front lags behind in terms of key indicators such as literacy, primary-level participation rate, basic health facilities, population welfare, water and sanitation, etc. Pakistan ranked 145th out of 179 countries in the world on the human development index in 2011.